The Early to Middle Ordovician graptolite faunal succession of the Trail Creek region, central Idaho, U.S.A - J. Maletz; D. Goldman; M. Cone (Geologica Acta, 2005)
The Middle Ordovician graptolite biostratigraphy of the Trail Creek region of Idaho is reviewed and revised. The oldest known fauna belongs to the Didymograptellus bifidus Biozone. The Isograptus victoriae lunatus, I. victoriae maximodivergens, Oncograptus, Undulograptus austrodentatus and Holmograptus lentus Biozones can be differentiated. Pseudophyllograptus archaios (Braithwaite) is found for the first time in the Trail Creek region. This species represents a conspicuous North American mid-continent faunal element and enables the correlation of the endemic P. archaios-C. flexilis Biozone of Utah with the D. bifidus Biozone of the Pacific faunal realm, thus, providing an important tool for the correlation of endemic mid-continent faunas with the pandemic deep water graptolite faunas.